Когенераційна система виробництва та споживання біогазу - Чайковська, Є. Є. (НТУ "ХПІ", 2014)
Запропоновано регулювання співвідношення виробництва теплоти та електричної енергії на основі прогнозування зміни параметрів технологічного процесу здобуття та споживання біогазу. Розроблена когенераційна система, що дозволяє приймати рішення на підтримку процесу зброджування, відвантаження та завантаження сировини та акумулювання електроенергії. Такий підхід дозволяє підвищити товарність біогазової установки та знизити собівартість виробництва електроенергії до (10–15) %. Економія біогазу, наприклад, при зброджуванні 60,2 т/добу сировини складає 49,4 тис. м 3/рік, що дає річне зниження викидів двоокису вуглецю 75,6 т/рік.

Heat-to-electric energy production ratio control was proposed based on the prediction of a change in the parameters of biogas consumption and production processes. The cogeneration system that allows for the decision making with regard to the fermentation process maintenance, raw material handling and electric power storage has been developed. The conditions of continuous biogas output and no losses of the generated heat for the fermentation process maintenance allow for the accumulation of the generated energy, which can be used not only to provide the operation of heat pump compressor but also during the period of the chargeback production of electric energy. Such an approach allows for an increase in the marketability of the biogas unit and a decrease in the price cost of electric energy production down to (10 to 15 %). The biogas saving, for example, during the raw material fermentation in amount of 60,2 t/day is equal to 49,4 m³/hour, which gives an annual decrease in the carbon dioxide emissions in amount of 75,6 t/year. Moreover, the waste of anaerobic fermentation can be used not only as a low-potential source of energy but also as the fertilizer, which satisfies environmental protection conditions.
Biogas production and consumption cogeneration system
Keywords: біогазова установка; тепловий насос; електроакумулювання; cogeneration; biogas unit; heat pump; electroaccumulation